A new Eumerus hoverfly (Diptera: Syrphidae) from Namibia and South Africa, with notes on similar species - Ricarte, Antonio; Hauser, Martin; Kinnee, Scott; Marcos-García, Mª Ángeles (Zootaxa, 2020)
Within the pollinator family Syrphidae, Eumerus Meigen, 1822 is a diverse genus with over 70 species recorded in the Afrotropical Region. A new species is described here from Namibia and South Africa. Adults are small to medium size flies, with spur-like expansions in the metatarsomeres 2 and 3. DNA sequences of the Cytochrome c oxidase subunit I (COI) gene were obtained from Namibian specimens. This is only the second Eumerus species documented from Namibia, where it was recorded from The National Botanic Garden, Windhoek. The new species is compared with similar species such as Eumerus vestitus Bezzi, 1912, for which a lectotype is designated. In addition, a new and preliminary morphological concept of the Eumerus obliquus group is proposed and a key to its African species is provided.